Formulating Criminal Law Policy for Social Conflict Resolution Based on North Maluku Indigenous Wisdom - Faisal Faisal; Absori Absori; Arief Budiono; Achmadi Achmadi; Reema Bhattacharya (Journal of Law and Legal Reform, 2026)
This study aims to analyze the local wisdom function of customary communities in North Maluku, Indonesia, as a conflict-resolution mechanism that emphasizes reconciliation before the formal criminal proceedings stage, to prevent excessive criminalization. This research analyzes customary values from four sultanates (Moloku Kie Raha), which may be integrated into criminal law policies as a form of legal reformation. Implementing ultimum remedium and restorative justice principles. This research employed a normative-empirical legal research method, drawing on approaches from legal sociology and legal pluralism. The analysis examined conflict-resolution mechanisms, with a focus on reconciliation in customary communities in North Maluku. Primary legal materials included the 1945 Constitution. Meanwhile, empirical data were obtained by identifying customary conflict resolution practices. Key Findings this research is North Maluku customary community’s local wisdom effectively functions as a pre-criminal conflict resolution through three main mechanisms which is orientation transformation from individual retaliation to the recovery of collective-spiritual balance, The use of customary oaths and rituals as instruments of moral evidence (such as in the Sopik tradition) as a moral evidencing instrument with a high level of compliance, and Deliberation through customary institutions, which emphasize reconciliation rather than the sanction of imprisonment. Implications of the findings for broader legal reform could address the sociological and philosophical aspects of customary conflicts. Thus, social harmony has been achieved, thereby strengthening restorative justice and the principle of ultimum remedium within Indonesia’s criminal justice system.